Fiberfox: Facilitating the creation of realistic white matter software phantoms - Neher, Peter F.; Stieltjes, Bram; Maier-Hein, Klaus H.; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2014)
Purpose: Phantom-based validation of diffusion-weighted image processing techniques is an important key to innovation in the field and is widely used. Openly available and user friendly tools for the flexible generation of tailor-made datasets for the specific tasks at hand can greatly facilitate the work of researchers around the world.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Artifact simulation; Diffusion-weighted imaging; Open-source software; S synthetic white matter fibers; Software phantoms